Reducing Postsurgical Wound Complications: A Critical Review. (June 2017) - Delmore, Barbara; Cohen, Joshua Mitchell; O'Neill, Daniel; Chu, Andy; Pham, Vinh; Chiu, Ernest
Abstract : GENERAL PURPOSE: To provide information on risk factors for surgical site infections (SSIs) and actions to mitigate that risk. TARGET AUDIENCE: This continuing education activity is intended for surgeons, surgical teams, physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant should be better able to: 1. Identify modifiable risk factors associated with the development of SSIs. 2. Select steps to mitigate the risks for and morbidity from SSIs. ABSTRACT: Given the current reimbursement structure, the avoidance of a surgical site infection (SSI) is crucial. Although many risk factors are associated with the formation of an SSI, a proactive and interprofessional approach can help modify some factors. Postoperative strategies also can be applied to help prevent an SSI. If an SSI becomes a chronic wound, there are recommended guidelines and strategies that can foster healing.